Vaginal flora in preterm premature rupture of membranes and their sensitivity to commonly used antibiotics - Shikha Rani (Asian Journal of Medical Sciences, 2014)
Background: Ascending infection is one of the most common etiologies in preterm premature rupture of membranes (PPROM). Antibiotics are used in PPROM to prolong the pregnancy and to prevent infection. But to prevent drug overuse and resistance, microorganism directed antibiotics should be used. So, this study was planned to evaluate vaginal flora in pregnant women with PPROM and their sensitivity to commonly used antibiotics.